2019
DOI: 10.1002/jccs.201800324
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethyldisiloxane‐modified ZnO‐SiO2‐coated superhydrophobic textiles for antibacterial application

Abstract: A superhydrophobic cotton textile with high antibacterial properties has been fabricated. The cotton textile was coated through the in situ growth of ZnO-SiO 2 nanoparticles in presence of chitosan as the template agent via a hydrothermal process at 95 C. This process was followed by the coating of additional layers of hexadecyltrimethoxysilane (HDTMS). The obtained cotton textile showed antibacterial property against Staphylococcus epidermis and Escherichia coli with inhibition zones up to 18.26 and 8.48 mm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…On this surface, only water and water droplets with low SDS concentration were primarily in the Cassie–Baxter state. [ 13–15 ] In contrast, both surfaces of glass slides B (beeswax emulation) and C (SiO 2 and TiO 2 ) were only hydrophobic and oleophobic, but with a high CA hysteresis (RAs >10°), exhibiting that the wetting states were more like the Cassie state. It demonstrated that superhydrophobicity was hard to form by low‐surface‐energy material (beeswax) alone or only simple roughness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On this surface, only water and water droplets with low SDS concentration were primarily in the Cassie–Baxter state. [ 13–15 ] In contrast, both surfaces of glass slides B (beeswax emulation) and C (SiO 2 and TiO 2 ) were only hydrophobic and oleophobic, but with a high CA hysteresis (RAs >10°), exhibiting that the wetting states were more like the Cassie state. It demonstrated that superhydrophobicity was hard to form by low‐surface‐energy material (beeswax) alone or only simple roughness.…”
Section: Resultsmentioning
confidence: 99%
“…In order to prepare a superhydrophobic coating for sorting liquid droplets, an ethanol suspension composed of beeswax and/or both nanoparticles of TiO 2 (25 ± 5 nm) and SiO2 (7-40 nm) was sprayed on four glass slides. [13][14][15] Considering that surfactants could significantly reduce the surface tension of the liquid, a series of sodium dodecyl sulfate (SDS) solution with different concentrations were selected to investigate their wetting performance and the sorting ability using the fabricated coatings. 16 From the results in Figure 1 (left), the surface of glass slide A displayed very high CAs (155.0 ) and very low CA hysteresis with water (3.9 ), indicating it is superhydrophobic.…”
Section: Preparation Of Superhydrophobic Coatingsmentioning
confidence: 99%
“…Penelitian lain dari Pradipta dkk [13] menjelaskan pembuatan kitosan-SiO2 dengan metode sol-gel sebagai agen hidrofobik pada kain rayon. Penelitian Mulyawan dkk [14] juga membahas peningkatan sifat hidrofobik pada kain kapas dengan suspensi ZnO dan asam stearat selain itu, penelitian Rilda dkk mengenai pembuatan tekstil superhidrofobik berlapis ZnO-SiO2 dengan modifikasi heksametildisiloksan sebagai antibakteri [15]. Berdasarkan penelitian sebelumnya komposit kitosan dan ZnO dapat digunakan sebagai agen hidrofobik dalam pelapisan pada kain katun.…”
Section: Pendahuluanunclassified
“…Recently, development of smart textiles has marched progressively in numerous applications such as antimicrobial, water treatments, catalyst, and photovoltaic devices . One of the existing methods to produce smart textiles is by combining them with nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently, development of smart textiles has marched progressively in numerous applications such as antimicrobial, water treatments, catalyst, and photovoltaic devices. [5][6][7] One of the existing methods to produce smart textiles is by combining them with nanomaterials. Nanomaterials are intended to enhance textile features such as self-cleaning, waterrepellent and dirt-repellent, antimicrobial, conductive, and antistatic properties, and decreased gas permeability and flammability.…”
mentioning
confidence: 99%